THE LEGAL IMPLICATIONS OF THE DISSYNCHRONIZATION IN THE REGULATION OF RESTORATIVE JUSTICE WITHIN THE CRIMINAL JUSTICE SYSTEM IN INDONESIA FROM THE PERSPECTIVE OF LEGAL CERTAINTY - Dhia Fadlia; Prija Djatmika; Yuliati (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2024)
The regulation of restorative justice within the criminal justice system in Indonesia is currently governed by the respective law enforcement agencies, but it has not been codified in the Indonesian Criminal Procedure Code (KUHAP), which can lead to legal uncertainty. Consequently, there are legal implications arising from the lack of synchronization in the regulation of restorative justice within Indonesia’s criminal justice system, particularly from the perspective of legal certainty. Therefore, this study aims to reconstruct the regulation of restorative justice to ensure legal certainty in the future. This research is a normative-juridical study utilizing both statutory and synchronic approaches. There are fundamental differences concerning the conditions and limitations of criminal acts as regulated by Police Regulation No. 8 of 2021, Prosecutor's Regulation No. 15 of 2020, and Supreme Court Regulation No. 1 of 2024. The existing partial guidelines on restorative justice, particularly regarding the conditions set forth, are inconsistent and cause legal uncertainty in determining which cases may be eligible for restorative justice, especially those under the Police institution, where the criteria are considered overly broad. Thus, the differences in restorative justice regulations among the respective agencies lead to inconsistencies in the conditions and limitations of criminal acts, as well as confusion in the restorative justice process during the investigation and inquiry stages within the Police. There is a need for specific regulation on restorative justice to be incorporated into the Criminal Procedure Code (KUHAP) to avoid inconsistencies and legal uncertainty.